Complete larval development of Thor amboinensis (De Man, 1888) Decapoda: Thoridae) described from laboratory-reared material and identified by DNA barcoding - Bartilotti, Cátia; Salabert, Joana; Santos, Antonina Dos (Zootaxa, 2016)
Of the 12 species of Thor described until present date, only three (25%) have their complete larval development known. Present work describes the complete larval development of Thor amboinensis, based on laboratory-reared material. The spent females were identified through the analysis of the partial sequences of the mitochondrial DNA barcode, also used for the reconstruction of the phylogenetic relationships within the recently resurrected and recognized family Thoridae Kingsley, 1879. Eight zoeal stages and one decapodid complete this species larval development. In the genus Thor, the number of zoeal stages varies greatly from two (T. dobkini) to eight (T. amboinensis and T. floridanus). The larvae of T. ambionensis and T. floridanus are readily distinguished from each other by the ornamentation of the ventral margin of the carapace and the pereiopods development. The first zoeal stage of T. amboinensis described by Yang & Okuno (2004) and the one described in present study are very similar. A brief discussion on the morphological characters and on the number of zoeal stages of the genus, as well as of the previous larval descriptions is made. The phylogenetic analysis suggest cryptic speciation for geographical separated populations of T. amboinensis, paraphyly of the genus Eualus, and the reassignment of E. cranchii to a different genus.